PhysiCan - a device for automatic CPM exercises implementation over canines: Design and analysis. (10th December 2022) - Erazo, A.; Cisneros, S.; Esparza, R.; Jumbo, M.; Choi, Y.; Ko, S.
Abstract: Continuous Passive Motion (CPM) devices have been used to assist physicians conducting human rehabilitation; however, similar machines specific for canine rehabilitation have not been found in the reviewed literature. This research performed a physical analysis of the hind limb of dogs to design a device for implementing automated CPM exercises. The device proved to comply with the guidelines to perform CPM exercises, allowing a proper setting of parameters to generate rehabilitation routines customized for different rehabilitation requirements. Also, an electromyography acquisition module was incorporated into the system, with surface electrodes to visualize and provide feedback to the user for muscle activation. Limitations were encountered with a range of motion of 80° and an error of approximately 2% for angular position accuracy. Highlights: Passive range of motion exercises enhance timely motion recovery. Continuous passive motion devices are not available for canine use. Powered orthosis as medical assistant in rehabilitation purposes for veterinarians. Surface electromyography as a tool for rehabilitation information feedback.